UiTM Street Law: a digital teaching and learning platform / Haswira Nor Mohamad Hashim ... [et al.] - Mohamad Hashim, Haswira Nor; Abdul Rahman, Noraiza; Mohamed Zain, Fazlin; Mahmood, Anida; Hasmin, Nor Akhmal; Mohamad Mangsor, Mazlina; Ganti Shaari, Ganti Shaari (Universiti Teknologi MARA, Kedah, 2023)
This paper discusses the establishment of the UiTM Street Law project in Malaysia and the launch of the UiTM Street Law Portal, which aims to educate the public about law and government through interactive teaching methods. Inspired by international Street Law movements, the UiTM Street Law programme aims to fill the gap in legal education initiatives within Malaysian law schools. While Malaysia has active community legal services, they do not resemble the comprehensive operations of the Street Law movement. To address this, the UiTM Street Law movement was founded to provide open-source legal materials and pro-bono education online. The project seeks to reach marginalized groups and offers core law subjects like contract law and constitutional law on the UiTM Street Law Portal. The portal includes interactive features for communication and scheduling pro-bono legal teachings. The project aligns with the Sustainable Development Goals of reducing inequality and promoting peace, justice, and strong institutions. By promoting access to legal knowledge and empowering marginalised communities, the UiTM Street Law project aims to contribute to a more equitable society and strengthen the justice system.